Digital marketing : strategic planning and Integration - Annmarie Hanlon (New Delhi Sage Publications, 2023)
An unbiased approach to the latest digital marketing models, offering students and practitioners a range of tools to implement in their digital marketing planning and strategy. Covering all aspects of digital marketing planning, the book aims to provide a roadmap for a digital marketing journey. This book has been structured to map the development of a digital marketing plan and concludes with a ready-made plan template to download and adapt. In addition, the content is supported by case examples from real-world organizations, and a number of pedagogical features throughout the chapters. The book is suitable for digital and e-marketing courses as well as professional courses for anyone interested in gaining a holistic understanding of digital marketing. Key features: smartphone sixty seconds features in every Chapter to evaluate influencers in relation to the topic covered digital tool boxes introduce professional tools ethical insights provide a reflective and challenging look at social issues and the negative sides of marketing.
Keywords: Management of Marketing